›Instrumenta domestica‹ aus Pompeji und ihr Design Eine Untersuchung zur decorativen Gestaltung der Kleinfunde aus Insula I 10 - Hielscher, Adrian (Decorative Principles in Late Republican and Early Imperial Italy (Decor), 2022)
Houshold objects (instrumenta domestica) from the Insula del Menandro are used to examine decorative principles, their correlation and interaction. Ancient object design is not only an expression of a visual culture, but rather an active part of it, as the objects are associated with activities, visual perception and semantic interpretation. These objects of Roman everyday life reflect cultural knowledge, social norms, values and lifestyles.